KINETIC STUDY OF THE UTILISATION OF DIFFERENT SUBSTRATES TO LACTIC ACID USING Lactobacillus delbrueckii - Abdullah Abdullah; Hanapi bin Mat; Widayat Widayat (METANA, 2012)
Abstract   Lactic acid fermentation includes several reactions in association with the microorganism growth.  A kinetic study was performed of the utilisation of multiple substrates to lactic acid using lactobacillus delbrueckii. Batch fermentation was performed to study effect of different substrates such as glucose, fructose and sucrose. The objective of this research is to study kinetics grow microbial. A anaerobic fermentation were studied in 3 litres stirred fermentor ( Biostat B Model) with working volume of 1 liter, temperature : 40 oC, pH = 6.0, inoculums size : 5% , sugar concentration =  20 g/1. During the first hours of fermentation, glucose and fructose accumulated in the medium and the rate of  hydrolysis of sucrose to glucose and fructose was faster than conversion of these substrate. The maximum concentration of glucose and fructose was 5.82 and 5. 14 g/l respectively. The sucrose, glucose, and fructose consumption completely utilized at 56, 68, and 104 hours, respectively. Kinetic parameter for maximum .specific growth rate in glucose, fructose and sucrose is 0.103, 0.0448, and 0.0398 (h-1), respectively. The saturation constant is 2.13, 2.67, and 3.32 g/1.   Key Words: Kinetic Study, Sugars, Lactic Acid, Maximum Specific Growth Rate and Saturation Constant